Pengaruh Keterlibatan Pelanggan, Pemasaran Daring, Konten Media Sosial, dan Siaran Langsung Terhadap Keputusan Pembelian Daviena Skincare - Dewi Novita Sari; Rafikhein Novia Ayuanti; Zulfia Rahmawati (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2025)
This study explores the impact of Customer Engagement, Online Marketing, Social Media Content, and Live Streaming on purchasing decisions from the Daviena Skincare Ori Pusat TikTok account. It uses a quantitative approach, gathering primary and secondary data through observation, literature review, documentation, and surveys. A non-probability sampling method with accidental sampling was used, involving 120 respondents who had made purchases from Daviena Skincare Ori Pusat. Data analysis was performed with multiple linear regression using SPSS 25. The results of the study indicate that the variables of customer involvement, online marketing, social media content, and live streaming have a partial and positive effect on purchasing decisions on the Daviena Skincare Ori Pusat. Simultan. The variables of customer engagement, online marketing, social media content, and live broadcasts have a positive effect on purchasing decisions on the Daviena Skincare TikTok account. The variable that has the most dominant effect on consumer satisfaction through the partial (t) test is the live broadcast variable. The coefficient of determination (R²) test result of 0.810 means that customer engagement, online marketing, social media content, and live streaming simultaneously contribute 81% to consumer satisfaction, while the remaining 19% is the variable.